Fiscal policy response of local governments to floods in Italy - Chiara Lodi; Giovanni Marin; Marco Modica (Fondazione Eni Enrico Mattei (FEEM), 2022)
This paper aims at empirically testing the dynamics of budget outcomes of Italian municipalities in the aftermath of floods, by accounting for heterogeneous levels of resilience and vulnerability to natural disasters. Our findings, based on a dynamic difference-in-difference after propensity score matching, point to substantial impacts in terms of increased capital expenditure and revenues from transfer, which also depend on the degree of resilience and vulnerability. Through our analysis we account for multiple aspects of risk so we can support policy decisions related to both ex-ante and ex-post disaster occurrence management.
Keywords: H2; H72; Q54; 330; Floods; Fiscal Policy of Local Governments; Resilience; Vulnerability